The fall of the Amazing Zalindas - Mack, Tracy. (Mack, Tracy. Sherlock Holmes and the Baker Street Irregulars ;, 2006)
The ragamuffin boys known as the Baker Street Irregulars help Sherlock Holmes solve the mysterious deaths of a family of circus tightrope walkers.